On the hydrology of the Partnach area in the Wetterstein mountains (Bavarian Alps) - Wetzel, Karl-Friedrich (ERDKUNDE, 2004)
Until today there is still a deficit in understanding the hydrology of alpine environments. Especially in times with changing climatic conditions it is necessary to get a better knowledge of the water resources in mountainous areas, because these areas are receiving disproportionate amounts of rainfall and in consequence they have high significance for the fresh water supply of large areas. During the summer months of 1996 and 1997 runoff, electrical conductivity and rainfall have been measured at the Partnach spring (Wetterstein mountains with the Zugspitze 2,962 m a.s.l.). These data are the first continuous hydrological records of the Partnach spring in the highest situated karst area of Germany. During both years of measurement, about 30% of runoff in summer is constituted by snow-melt processes in the upper part of the catchment. In the dry autumn of 1997 snow-melt hydrographs of the glacier fields can be seen clearly over several weeks. With the construction of the recession curve the overall depletion behaviour of the catchment has been demonstrated. Recession limbs of several storm-induced runoff events constitute the upper part of the recession curve, depletion of the groundwater takes place if runoff reaches values lower than 2 m³/s. With graphical and geochemical methods it has been shown that runoff is produced by different karst water systems with specific velocities of flow. Apart from overland flow, three components of groundwater flow have been detected. Flow in karst conduits, flow in fractures and diffuse Darcian flow in fine fractures are reacting with a different delay after storm precipitation. Displacement processes for all components of flow can be observed by means of electrical conductivity. Old pre-event water with a high electrical conductivity is pushed out of the aquifer before the new storm water can be detected by a falling electrical conductivity in the karst spring. Flow velocities in the karst conduits have been calculated during snow-melt. The rhythmic curve of the daily melting hydrographs is connected with a stepwise fall of the electrical conductivity at the karst spring because of dilution processes. New melting water arrives at the Partnach spring when the electrical conductivity is falling. By means of the electrical conductivity, mean velocities of flow of about 400 m/h (about 11 m/s) have been calculated. In comparison with Dinaric karst areas, these high values are pointing to a well developed karst conduit system in the underground of the Partnach area.